(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Retinal disorders in patients with Alzheimer’s disease (AD) are given special attention. Purpose: To identify optical coherence tomography (OCT)-based retinal structural changes in patients with mild or moderate AD. Materials and Methods: Forty-five AD patients (88 eyes; age, 66.2 ± 3.44 years) with mild or moderate cognitive impairments were involved into the study. All subjects underwent a conventional eye examination and OCT measurements. For Cirrus HD-OCT imaging, the Macular Cube 512 ? 128 Combo protocol was used. The RNFL, retinal ganglion cell layer (RGCL), and internal plexiform layer (IPL) thicknesses were determined using RNFL and ganglion cell complex (GCC) protocols. Results: Compared with controls, patients with AD had 53.2% lower Mini Mental State Examination (MMSE) scores (p < 0.05). In addition, RNFL thicknesses in the temporal, superior and inferior quadrants in patients with AD were significantly (31.4%, 21.8% and 33.1%, respectively; p < 0.05) thinner compared to controls. Moreover, compared to controls, focal loss volume (FLV) and global loss volume (GLV) of GCC in AD patients were 1.7 times (p < 0.05) and 2.8 times (p < 0.01), respectively, increased, whereas central macular thickness, overall macular cube volume and average macular cube thickness were 14%, 17.8% and 3.5% decreased. Conclusion: Our findings confirm the reports of changes in the retinal structure in patients with mild or moderate AD, particularly, the decreased GCC thickness and increased GCC FLV and GLV.